1992
DOI: 10.1002/gcc.2870050104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromosome 12 aneuploidy in interphase cells from human male germ cell tumors by fluorescence in situ hybridization

Abstract: The i(12p) marker chromosome has been found to be a highly nonrandom chromosome abnormality associated with germ cell tumors (GCTs). We have previously shown that a chromosome 12 centromere specific alpha-satellite DNA probe detects the i(12p) by virtue of differences in the size of the signal originating from the i(12p) and normal chromosome 12 centromeres after fluorescence in situ hybridization (FISH) in metaphase and interphase cells of cultured GCT cell lines. We have now extended this analysis to 72 fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Since the formation of the isochromosome includes the centromeric/pericentromeric region of chromosome 12, the abnormality can be detected using commercially available chromosome 12 centromeric fluorescent in situ hybridization (FISH) probes. 67,68,71 In a metaphase spread these will show the isochromosome nicely. In interphase cells one can detect a numerical abnormality (normal chromosome 12 plus the number of isochromosomes present) but it is more difficult if not impossible to state that an isochromosome is indeed present.…”
Section: Molecular Biology Of Germ Cell Tumorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the formation of the isochromosome includes the centromeric/pericentromeric region of chromosome 12, the abnormality can be detected using commercially available chromosome 12 centromeric fluorescent in situ hybridization (FISH) probes. 67,68,71 In a metaphase spread these will show the isochromosome nicely. In interphase cells one can detect a numerical abnormality (normal chromosome 12 plus the number of isochromosomes present) but it is more difficult if not impossible to state that an isochromosome is indeed present.…”
Section: Molecular Biology Of Germ Cell Tumorsmentioning
confidence: 97%
“…This genetic abnormality occurs in all primary sites and histologic types. 66,67 Approximately 80% of cases have i(12p) and the remainder have excess 12p genetic material in derivative chromosomes. 68 The consistent gain of 12p genetic material is supported by gene array and comparative genomic hybridization data.…”
Section: Molecular Biology Of Germ Cell Tumorsmentioning
confidence: 99%
“…This anomaly is found less frequently in seminomas (SE), composed of malignant counterparts of early germ cells, than in nonseminomatous TGCT (NS), which are caricatures of early embryonal development composed of embryonal (embryonal carcinoma (EC] and teratoma (TE)) and/or extraembryonal (yolk sac (YS) and choriocarcinoma (CH)) components [9,10], Fluorescence in situ hybridization (FISH) using region-specific probes showed that also i(l2p)-negative TGCT invariably exhibit overrepresentations of 12p-sequences [11,12], Because conventional cytogenetic information is derived from mitotic cells, such data may be biased due to selection of 0165-4608/96/$15.00 PII S0165-4608(96)00043-X subpopulations of cells by the methods of direct harvest ing or short-term in vitro culture. This has recently been suggested for SE with respect to the presence of i(12p) [13]. Also the presence of markers of which, by definition, the chromosomal origin can not be determined, may ham per the identification of certain chromosomal regions important for the development of this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other groups have reported that 12p gain is not an early event, but rather relates to the invasive growth of TGCTs (Rosenberg et al, 2000;Summersgill et al, 2001). An isochromosome of the short arm of chromosome 12, i(12p), has been proposed as a specific genetic marker of human TGCTs (Rodriguez et al, 1992). The same group recently reported that among 101 TGCT specimens, stem cell-associated genes that localize on chromosome 12p13.3 are overexpressed in seminomas and embryonal carcinomas (Korkola et al, 2006).…”
Section: Introductionmentioning
confidence: 99%